Perceptions about different shades of skin colour and attitudes towards pigmentation in the 'black' African community - Nkwadi, Palesa (My University, 2016)
Variations and differences in skin colour has been a complex phenomenon around the world. Issues of colour and identity in a postcolonial and post-Apartheid context, is also a significant field of interest. Popular stereotypes portray darker skin pigmentation as undesirable and inferior to lighter pigmentation. The process of ‘lactification’ (Fanon, 1968) remains a question today as much as during earlier colonial times. These stereotypes also bring to the fore, essential questions about hierarchies of power and oppression, culture and identity and how these are shaped to fit popular dominant culture. This study explored peoples’ perceptions around different shades of skin colour and attitudes towards various shades of pigmentation. The study adopted a qualitative approach and explored perceptions around skin colour through in-depth interviews. Fifteen adult participants in Soweto, Gauteng were recruited for the study via purposive sampling. The data collected was analysed using thematic content analysis. The study found that the western idea of attractiveness is still highly regarded. Black women and men take various measures to conform to the western ideal simply to be acknowledged as attractive and stigma is attached to the dark complexion. Self-esteem is affected by the perception of beauty, high perception of attractiveness equals to the high self-esteem.
Keywords: Colonialism; Colourism; Identity; Social perceptions; Whiteness; Blackness